سعودی عرب کے ادبِ سیرت میں فقہیاتِ سیرت: تحقیقی جائزہ Jurisprudential discourses in Saudi Arabian Sīrah Literature: An Analytical Study - Dr. Muhammad Umair Raouf; Dr. Hafiz Muhammad Naeem (jihat-ul-islam, 2026)
The jurisprudential methodology، commonly referred to as Fiqh al-Sīrah، represents a distinctive and increasingly influential approach in the study of the Prophetic biography (Sīrah). Although often highlighted in contemporary scholarship، this methodology is deeply rooted in classical Islamic literature، as evidenced by the works of renowned scholars such as Imām ʿAbd al-Raḥmān al-Suhaylī، Imām Ibn Qayyim al-Jawziyyah، and Yaḥyā ibn Abī Bakr al-ʿĀmrī. In recent decades، numerous contemporary Sīrah scholars، particularly from Saudi Arabia، have adopted and further developed this jurisprudential lens in their analysis of the Prophet Muḥammad’s (PBUH) life. This study critically examines the contributions of Saudi scholars to Fiqh al-Sīrah، focusing on how they derive legal rulings (aḥkām) and ethical lessons from key events in the Prophet’s life. Their methodological approach reflects both analytical depth and contemporary relevance in interpreting the Sīrah for legal and social application. Notable works discussed include Fiqh al-Sīrah by Dr. Zayd ʿAbd al-Karīm al-Zayd and Dr. Munīr al-Ghaḍḍābān، which exemplify rigorous efforts to extract juridical guidance from historical narratives. The paper also presents detailed case studies of seminal Saudi texts such as Al-Sīrah al-Nabawiyyah by Aḥmad Zaynī Daḥlān، Al-Sīrah al-Nabawiyyah al-Ṣaḥīḥah by Dr. Akram Ḍiyāʾ al-ʿUmarī، and Al-Aṭʿimah wa al-Ashribah fī ʿAhd al-Rasūl by Dr. Muḥammad ibn Fāris al-Jamīl. These works illustrate a sustained emphasis on extracting legal rulings from various aspects of Prophetic conduct، including dietary practices، military engagements، and socio-cultural norms. The research concludes that the Saudi scholarly tradition provides a robust and methodically structured contribution to Fiqh al-Sīrah، significantly enriching contemporary understandings of both the legal and moral dimensions of the Prophet’s life.